How Children Understand Civic Actions: A Mixed Methods Perspective. (September 2016) - Metzger, Aaron; Syvertsen, Amy K.; Oosterhoff, Benjamin; Babskie, Elizabeth; Wray-Lake, Laura
The development of civically engaged citizens is vital for democratic societies. Although several studies have explored children and adolescents' conceptualizations of civic engagement, less is known about youths' understanding of the individual skills and attributes best suited for civic action. The current study utilized a Q-sort methodology to explore the types of character strengths children and adolescents ( n = 87; M age = 13, 9-19, 52% female) assigned to people who engage in different types of civic activities. Participants sorted 12 character strengths (amazed, creative, forgiving, future-minded, generous, grateful, humble, joyful, leader, purposeful, responsible, and thrifty) into five categories ranging from "most like" to "least like" based on their perceptions of individuals engaged in four distinct civic activities: volunteering, voting, protesting, and engaging in environmental or conservation behaviors. Youth not only differentially applied certain character strengths to individuals engaged in distinct civic activities but also identified a set of character strengths (future-minded, leader, purposeful, and responsible) as core to multiple forms of civic engagement. Results provide new insights into youths' budding conceptualization of the individual characteristics, attributes, and motivations, which undergird different forms of civic action. Qualitative analysis of youths' justifications for their rankings provided additional nuance into their developing understanding of civic actions.